An optical fibre sensor for remotely detecting water traces in organic solvents. Issue 85 (30th August 2016) - Han, Mengke; Chen, Ming; Ebendorff-Heidepriem, Heike; Fang, Cheng; Qin, Anjun; Zhang, Hu; Tang, Ben Zhong; Tang, Youhong; Ruan, Yinlan
Abstract : Tetraphenylpyrazine-triphenylamine detects water traces by fluorescence peak wavelength shifting and optical fibres were used for a remote and field-deployable sensing ability. Abstract : Tetraphenylpyrazine-triphenylamine (TPP-TPA) was used to detect water traces in organic solvents by monitoring the shift of the fluorescence peak wavelength. This wavelength based method avoids the intrinsic problems of fluorescence intensity change based methods. The use of optical fibres for the detection provides a remote and field-deployable sensing ability.